Corporate finance : core principles and applications - Ross, Stephen A.; Westerfield, Randolph; Jaffe, Jeffrey F., 1946- (MCGRAW-HILL, 2011)
"Corporate Finance: Core Principles & Applications is rich in valuable learning tools and support to help students succeed in learning the fundamentals of financial management"--
Revised edition of the authors' Corporate finance, [2018]
Includes index.
Keywords: Corporations -- Finance